The Health and Well-being of Low Paying Jobs in Southern Africa: Case Study of Security Guards in Zambia - Tayali, Esnart Mwaba; Sakyi, Kwesi Atta (Advances in Social Sciences Research Journal, 2020)
As concerns for employee well-being across all sectors increase, security guards in Southern Africa and the rest of Africa at large attract less attention in human resource management. Well-being is pivotal for positive psychological feeling of workers, and also conducive for economic growth. Employee well-being has positive effects on company performance, profitability and growth. Therefore, employee well-being is a cardinal factor across the globe. Security guards, like any other employees, deserve decent conditions of service, which promote their overall well-being. Youths who lack sufficient funds to pursue tertiary education in universities end up undertaking the most affordable short courses in order to see them through employment, as they are desperate for incomes to sustain themselves and families. The commonest affordable short courses in Southern Africa include those found in jobs such as security guards, carpentry, tailoring, and cookery. Amongst the most affordable short courses, youths prefer security guard training due to its high job market demand. The health, safety, and quality of the physical environment, as well as the low subsistence wages for Security guards leave much to be desired. The labour standards of security guards in Africa are unthinkable, unsatisfactory and atrocious. This study aims at introducing essential recommendations in order to improve the well-being of security guards in southern Africa. The paper adopted a qualitative research approach by gathering information from security guards working in five different security firms in Zambia.